The use of Trichoderma harzianum to control the Bottom Pathogenic Fungus of Rice Seed (Oryza zativa L.) from breeders in Waeapo District, Buru Regency - Yohanis Sinay; A. Marthin Kalay; Maimuna La Habi (Faculty of Agriculture, Pattimura University, 2022)
Healthy seeds are needed to support the food crops growth and yield. This study was aimed to 1. identify the types of pathogenic fungi on rice seeds in Waeapo District, Buru Regency; 2. Asses the fungal pathogen effect on the growth of rice cv Ciherang seedings; and 3. determine the ability of Trichodema harzianum to control those fungus and its effect on the germination of rice. The research consisted of foure stages, namely 1. Isolation and identification of the bottom pathogenic fungi of rice seeds; 2. Pathogenicity test of the pathogens; 3. Antagonistic test of T. harzianum against pathogens in vitro, and 4. Bioassay of T. harzianum inoculation to pathogen-infected rice seeds. The research found that pathogenic fungi isolated from rice seeds from breeders in Waeapo District were Mucor sp., Sclerotium sp., Aspergillus sp., Rhyzoctonia sp., and Drechslera sp., which cause the rice seeds damage of 13.33 %, 10.37%, 11.85%, 11.11%, and 12.59% respectively. In vitro assay verified that T. harzianum was able to suppress the development of pathogens Mucor sp., Sclerotium sp., Aspergillus sp, Rhyzoctonia sp., and Drechslera sp. up to 46.99%, 67.48%, 55.83%, 55.42%, and 31, respectively. 60%. The inoculation of T. harzianum to infected rice seeds, reduced the rice damage by Mucor sp, Sclerotium sp, Aspergillus sp, Rhyzoctonia sp, and Drechslera sp, up to 79.14%, 18.72%, 17.97%, 18, respectively. 71% and 61.40% respectively.